Damage to germination of seed corn caused by mayze weevil Sitophilus zeamais and angoumois grain moth Sitotroga cerealella. - Santos, Jamilton P.; Maia, João Dimas G.; Cruz, Ivan (Pesquisa Agropecuaria Brasileira, 2014)
Damage by maize weevil and Angoumois grain moth (AGM) decreases the seed quality. Damaged seed if germinate produce a deficient plant. The life cycle of these insects, takes 35-50 days to complete. This research was undertaken to know the effect of these insects in their various developmental stages on germination. Comparing with the uninfested seed (control) with 95% germinative potential, the weevil preence in the egg stage (0-4 days old) reduced the germination in 13%, 1st instar larva (5-10 days) in 23%, 2nd instar (11-16 days) in 30%, 3rd instar (17-22 days) in 32%, 4th instar/pre-pupae (23-28 days) in 60%, pre-pupae/pupae (29-34 days) in 70% and pupae/adult (35-40 and 41-46 days) reduced germination in 94% and 93%. As to AGM only after 25 days the insect reduced germination significantly. Larvae of 3rd and 4th instar (25-30 dias) reduced in 43%, pupae (31-36 days) in 45% pupae/adult (37-42 e 43-48 days) in 49,7% and 63% the germination